2018
DOI: 10.14568/cp2018007
|View full text |Cite
|
Sign up to set email alerts
|

Fungal stains on paper: is what you see what you get?

Abstract: Mitigation of fungal biodeterioration on paper documents and artworks represents a challenge to conservators worldwide. Numerous lists of fungal species have been identified from paper collections, but are those species responsible for the respective biodeterioration phenomena or just environmental contaminants? The present work was aimed at obtaining an association between specific fungal stains and causative fungal species. 23 stains from three paper documents were sampled. Fungal structures observed in situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 45 publications
0
28
0
1
Order By: Relevance
“…For our study, we selected four fungal strains known to cause paper deterioration in archives, namely Chaetomium globosum, Penicillium chrysogenum, Penicillium glabrum and Aspergillus versicolor [8, 10, 11] plus one recently isolated wild type strain of the highly cellulolytic genus Trichoderma, T. capillare [32]. All of the five selected fungal strains were reported to have good cellulolytic capabilities [34-37], making them suitable for the evaluation of the antifungal potentials of ILs on paper-decomposing molds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For our study, we selected four fungal strains known to cause paper deterioration in archives, namely Chaetomium globosum, Penicillium chrysogenum, Penicillium glabrum and Aspergillus versicolor [8, 10, 11] plus one recently isolated wild type strain of the highly cellulolytic genus Trichoderma, T. capillare [32]. All of the five selected fungal strains were reported to have good cellulolytic capabilities [34-37], making them suitable for the evaluation of the antifungal potentials of ILs on paper-decomposing molds.…”
Section: Resultsmentioning
confidence: 99%
“…Exogenous abiotic factors, such as humidity and temperature for example, not only affect abiotic deterioration processes, but also facilitate microbial attack [7]. In a recent survey among 57 institutional participants from 20 different countries, Sequeira et al [8] have found that 79 % of the participants had to deal with fungal infestations even though common preventative measures against fungal deterioration had been undertaken. According to the authors, most of these infestations were caused by unforeseen water contact (floods, leakage, fire suppression, outdoor humidity) or failure of (micro-)climate control systems, illustrating the importance of this issue beyond (sub-)tropical areas [1].…”
Section: Introductionmentioning
confidence: 99%
“…Nesta intervenção mínima incluiu-se a limpeza superficial do bordado, a consolidação e preenchimento do papel perfurado de modo a reforçar a sua resistência colonização biológica não confirmou esta hipótese, pois, por um lado, só numa das oito amostras recolhidas para colonização biológica se observou microorganismos (fungos do género Aspergillus) e, por outro lado, o desenvolvimento desse fungo apenas numa zona marginal da caixa de Petri sugere que essa identificação, como acontece com alguma frequência [11], resultou de contaminação.…”
Section: Intervenção De Conservaçãounclassified
“…In a recent survey among 57 institutional participants from 20 different countries, Sequeira et al . [8] have found that 79% of the participants had to deal with fungal infestations even though common preventative measures against fungal deterioration had been undertaken. According to the authors, most of these infestations were caused by unforeseen water contact (floods, leakage, fire suppression, outdoor humidity) or failure of (micro-)climate control systems, illustrating the importance of this issue beyond (sub-)tropical areas [1].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive literature on deterioration-causing microorganisms, especially fungal isolates from libraries and archives, is available [611]. For example, Chaetomium globosum , Penicillium chrysogenum as well as other species of the respective genera were isolated from and identified as causative for dark stains in historic documents [8]. Species such as Aspergillus versicolor (among Aspergillus species) in addition to a diverse set of Trichoderma species were also reported to be ubiquitously found in archives, museums and libraries [10, 11].…”
Section: Introductionmentioning
confidence: 99%